Cornelius O'Dowd Upon Men And Women And Other Things In General - Lever, Charles, 1806-1872 (Salt Lake City, UT : Project Gutenberg, 2008)
"Cornelius O'Dowd Upon Men And Women And Other Things In General" by Charles Lever is a novel written in the mid-19th century. The book presents a humorous and satirical account of its protagonist, Cornelius O'Dowd, as he navigates various societal themes and personal anecdotes with a keen observation of human nature, particularly reflecting on men and women during his time. The opening of the tale introduces Cornelius O'Dowd, who reflects on his life experiences, character, and relationships. It provides personal insights into his failures and aspirations, including his brief foray into law, his military service, and his thoughts on love and society, particularly concerning his wife, Mrs. O'Dowd. Cornelius's witty commentary sets the stage for a narrative that blends personal narrative with broader societal observations, hinting at his future adventures and explorations of European landscapes, characters, and political affairs, particularly relating to Italy during a tumultuous period. (This is an automatically generated summary.)
Release date is 2008-05-20
Produced by David Widger
Keywords: Essays; Italy -- Description and travel; Biography -- Humor